Implementation of Inner Village Government Policy Community based Provision of Drinking Water and Sanitation Community-Based Drinking Water and Sanitation Provision Program (Case Study of Telaga Baru Village, Kepuluan Meranti Regency) - Rustam, Afrinaldy; Fauzi, Ahmad (JOELS: Journal of Election and Leadership, 2025)
This study examines the implementation of the village government's policy under the Community-Based Provision of Drinking Water and Sanitation (Community-Based Drinking Water and Sanitation Provision Program.) program in Telaga Baru Village, Kepulauan Meranti Regency. The core issue addressed is the effectiveness of the policy's execution, the challenges encountered during its implementation, and its impact on improving community access to clean drinking water and sanitation facilities. The objectives of this research are threefold: (1) to analyze the process of implementing the Community-Based Drinking Water and Sanitation Provision Program. program in Telaga Baru Village; (2) to identify the obstacles faced in achieving the program's goals; and (3) to evaluate the program's impact on the quality of life of the local community. Key findings reveal that the Community-Based Drinking Water and Sanitation Provision Program. program has contributed to enhancing community access to clean water and sanitation, though its implementation remains suboptimal due to financial constraints and limited community participation. The success of the program is closely linked to active community involvement, effective stakeholder coordination, and sustainable management practices. However, significant barriers include inadequate community awareness of sanitation's importance, insufficient supporting infrastructure, and delays in program funding allocation. This research provides valuable insights and practical recommendations to improve the strategies for implementing community-based water and sanitation policies, particularly in rural areas, ensuring long-term sustainability and broader positive impacts for local communities.who vote is still pragmatic, and an election system that provides space for the practice of kinship politics.